Guidance problems of students in the Sekolah Guru A/Sekolah Guru Taman Kanak-kanak Negeri of Salatiga (Indonesia) - Susilaradeya, R. Dulkaidja 1927- (Quezon City, Philippines College of Education, University of the Philippines Diliman, 1965)
This paper identifies common problems of the students in the Sekolah Guru A/ Sekolah Guru Taman Kanak-Kanak Negeri of Salatiga. The problem checklist data reveal that all the subjects of this study have had reported problems in school. The problem areas indicated (in the order of most to least frequent) are: school, leisure time, personality, social, home, religion, and health.
Thesis (Master of Education)--University of the Philippines Diliman
Keywords: Counseling in secondary education